Political Communication Strategy of Iwan Rahayu in the 2019 South Tangerang City Dprd Election Campaign - Purwanto*, Hari Eko; Muksin, Nani Nurani (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research aims to describe Iwan Rahayu's Political Communication Strategy in the 2019 Regional Representative Council (DPRD) Election Campaign in South Tangerang City. It explores Iwan Rahayu's Political Message during the 2019 DPRD Election Campaign in South Tangerang City. Additionally, it examines the Supporting and Hindering Factors faced by Iwan Rahayu during the same campaign. The study employs relevant theories, including political communication theory, political communication messages, supporting factors, and hindering factors. The research adopts a qualitative approach, utilizing a descriptive research method. asked for the discussion of the research findings, the results indicate the following: Firstly, Iwan Rahayu actively implemented a direct campaign strategy. The campaign team, along with Iwan Rahayu, conducted visits and fostered connections with every village by participating in various community activities. Moreover, door-to-door campaigns were still employed by candidate Iwan Rahayu. Group discussion campaigns involved forming small discussion groups focused on addressing issues faced by the community. Indirect mass campaigns were also conducted through print media, billboards, and banners. Secondly, Iwan Rahayu consistently conveyed the same political message during the campaign, emphasizing his commitment to assisting the community, as evidenced by ten years of dedicated development in the Pamulang electoral district.